2011
DOI: 10.1007/s00269-011-0426-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of polycrystalline Mg(OH)2 at 2 GPa: effect of grain boundary hydration–dehydration

Abstract: The effect of intergranular water on the conductivity of polycrystalline brucite, Mg(OH)2, was investigated using impedance spectroscopy at 2 GPa, during consecutive heating-cooling cycles in the 298-980 K range. The grain boundary hydration levels tested here span water activities from around unity (wet conditions) down to 10−4 (dry conditions) depending on temperature. Four orders of magnitude in water activity result in electrical conductivity variations for about 6-7 orders of magnitude at 2 GPa and room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 61 publications
0
10
0
1
Order By: Relevance
“…1 Microstructure of as-cast AZ91 alloy [39] generation distributed mainly around these two phases. However, once corrosion products deposited, the dominant hydrogen generation sites were on the surface of the corrosion products since it is highly possible that porous magnesium hydroxide filled with solution was electronically conductive [59], and that the involvement of Al corrosion products (identified by EDS, XPS, and XRD [35,37,39]) increased this conductivity [35,47]. This indicates that the location of the anodic and cathodic sites on the alloy surface shifted during corrosion as the corrosion products become active cathodic sites.…”
Section: Resultsmentioning
confidence: 99%
“…1 Microstructure of as-cast AZ91 alloy [39] generation distributed mainly around these two phases. However, once corrosion products deposited, the dominant hydrogen generation sites were on the surface of the corrosion products since it is highly possible that porous magnesium hydroxide filled with solution was electronically conductive [59], and that the involvement of Al corrosion products (identified by EDS, XPS, and XRD [35,37,39]) increased this conductivity [35,47]. This indicates that the location of the anodic and cathodic sites on the alloy surface shifted during corrosion as the corrosion products become active cathodic sites.…”
Section: Resultsmentioning
confidence: 99%
“…There is general agreement that the presence of water, or rather hydrous fluid, drastically promotes element transport along grain boundaries. For example, the grain boundary diffusivity of aluminium in 'hydrous fluid-saturated' rocks is enhanced by seven orders of magnitude compared to 'nearly anhydrous' rocks (Carlson 2010), and Gasc et al (2011) reported the same range of variations for the electrical conductivity in polycrystalline brucite from 'dry' to 'wet' conditions. Based on a consensus from literature, Farver and Yund (1995) proposed that intergranular diffusion can be classified into three categories, depending on water activity in the intergranular medium: 'water-absent', 'water-unsaturated' and 'water-saturated' regimes (see also Rubie 1986;Carlson 2010).…”
Section: Introductionmentioning
confidence: 82%
“…The stability and electrical conductivity of rocks [Fuji-ta et al, 2004;Kariya and Shankland, 1983;Olhoeft, 1981], minerals [Gasc et al, 2011;Guo et al, 2011;Guo and Yoshino, 2014;Reynard et al, 2011;Yang, 2011], graphite films on grain boundaries [Frost et al, 1989;Glover, 1996;Yoshino and Noritake, 2011], partial melts [ten Grotenhuis et al, 2005;Hermance, 1979;Lebedev and Khitarov, 1964;Roberts and Tyburczy, 1999], saline fluids [Glover and Vine, 1994;Guo et al, 2015;Hyndman and Hyndman, 1968;Hyndman and Shearer, 1989;Nesbitt, 1993;Shimojuku et al, 2012Shimojuku et al, , 2014, and CO 2 -H 2 O fluid [Nesbitt, 1993] have been investigated as explanations for the highly conductive zones. However, the conductive zones likely represent a composite of these materials, in which aqueous fluids are considered to be a dominant cause of the high conductivity [e.g., Guo et al, 2015;Hyndman and Shearer, 1989;Shankland and Ander, 1983], and this would be more plausible at subduction zone, since the dehydration of hydrous minerals would occur in the subducting slab [Ichiki et al, 2009;McGary et al, 2014;Reynard et al, 2011].…”
Section: Introductionmentioning
confidence: 99%